'What can I do? Any tips?' Online communities and agoraphobia, an open channel for shared participation in management of medical treatment - Jover-Leal, Assumpta; Grau-Muñoz, Arantxa (Revista de Antropología Social, 2021)
This article discusses the entries produced in three groups of the Facebook social network created and used by people diagnosed with agoraphobia through a discourse analysis. We identify that virtual communities constitute spaces that favour the emergence of an active positioning of their participants in the co-management of their medication from three axes: a) extra-medical space of equals that favors the exchange of information, training and consultation; b) space that makes possible the birth ans sharing of alternative narratives to the pharmacology, and; c) space of conflict between narratives about medication that, in some cases, works as a social catalyst of dissident pharmacological discourses. Given the existence of a single narrative about the treatment for agoraphobia from a medical point of view that does not fit equally into the diverse experiences of agoraphobic people, the groups we analyze turn out to be an opportunity to develop unmet needs, desires and questions, with the consequences that this entails for a virtual community that has constructed its meanings with a great presence of the medical discourse.
Keywords: mental health; agoraphobia; social network; drug treatment management; patient participation; Internet; decision making